Use of vitamin D to reduce lameness in broilers reared in harsh environments - Nääs, I de A; Baracho, M dos S; Bueno, LGF [UNESP]; Moura, DJ de; Vercelino, R do A; Salgado, DD (Fundação APINCO de Ciência e Tecnologia Avícolas, 2012)
In tropical poultry-producing countries, poultry houses usually have little environmental control. This study investigated the effect of dietary vitamin D on the incidence of leg abnormalities of a fast-growing broiler strain reared under harsh conditions. In this study, 300 one-day-old male broilers were distributed in two treatments with three replicates of 50 birds each. One group was fed a placebo and the other group was fed 25-hydroxycholecalciferol (25-OH-D3) in a soluble form. The environmental variables were weekly recorded during until birds were 49 days old. Birds were weekly gait scored, and their walking speed and vertical force while walking were assessed. Post-mortem examination was performed and skeletal lesions were assessed. Control birds presented more leg problems than those that ingested 25-OH-D3. These results suggest that dietary vitamin D is effective in decreasing the severity of lameness by reducing tibial dyschondroplasia and other leg abnormalities.
Keywords: Feet force measurement; leg abnormalities; vitamin D supplement